EAST AFRICAN POPULAR MUSIC. From Alex Seago, Richmond College, London, 1985. - Seago, Alex (International Library of African Music, 1987)
When compared to West and Central African popular music, East African music has received relatively little attention from music critics. The main reason for this seems to be that pop in East Africa has tended to be an imported, or at least, an imitated music. During the 60's and 70's the Zairean rhythms of Franco, Rochereau and Co. took Kenya, Uganda and Tanzania by storm to become firmly established as the dominant urban sound. Zairean musicians moved east to take up residences in the clubs and attracted huge crowds of Kenyan, Tanzanian and Ugandan fans.
Keywords: African Music